Design, synthesis and anticonvulsant activity of new Diacylthiosemicarbazides - Kholodniak, O. V.; Stavytskyi, V. V.; Kazunin, M. S.; Bukhtiyarova, N. V.; Berest, G. G.; Belenichev, I. F.; Kovalenko, S. I.; Холодняк, Олена Валеріївна; Ставицький, Віктор Валерійович; Казунін, Максим Станіславович; Бухтіярова, Ніна Вікторівна; Берест, Галина Григорівна; et al. (Kyiv: Institute of Molecular Biology and Genetics of the NAS of Ukraine, 2021)
Aim. A targeted search for anticonvulsant agents among unknown diacylthiosemicarbazides with the analysis of the structure-activity relationship (SAR-analysis). Methods. Organic synthesis; molecular docking; spectral methods; pentylenetetrazole convulsions, statistical methods. Results. A strategy of search for new anticonvulsant agents among unknown diacylthiosemicarbazides has been developed. It included virtual-oriented screening towards [the] active centers of enzymes and sodium channels that underlie the mechanism of antiepileptic drugs activity. The synthesis of diacylthiosemicarbazides was carried out by the in situ method, namely, accomplishing the interaction of cycloalkanecarbonyl chlorides with ammonium isothiocyanate and the subsequent nucleophilic addition of cycloalkyl- (aralkyl-, aryl-, hetaryl-) carboxylic acid hydrazides. The peculiarities of the structure of the synthesized compounds were confirmed by spectral methods (LCMS and 1H NMR spectra). Biological screening showed that diacylthiosemicarbazides (2) in the experimental model of pentyleneterazole seizures in rats increased the latency period of seizures by 2.77–7.82 times, reduced the duration of tonic-clonic seizures by 1.23–5.59 minutes and prevented mortality by 30–60 %, relative to the control group of animals. It was shown that diacylthiosemicarbazides (2.6, 2.15, 2.22, 2.18) with cyclopropane- or cyclopentanecarboxamide groups show the anticonvulsant activity that exceeds that of the reference drug Depakine or competes with it. Conclusions. A range of new diacylthiosemicarbazides were obtained and the primary screening of their anticonvulsant activity was performed, the SAR-analysis was provided, and the hit-compound was identified for further in-depth pharmacological studies.
Keywords: diacylthiosemicarbazides; design; synthesis; pentylenetetrazole convulsions; anticonvulsant activity